Endovascular treatment of extracranial carotid artery stenosis using a dual-layer micromesh stents: a systematic review. (3rd June 2021) - Mazzaccaro, Daniela; Giannetta, Matteo; Fancoli, Fabiana; Righini, Paolo; Nano, Giovanni
ABSTRACT: Introduction: We aimed to review the safety and effectiveness of dual-layer micromesh stents for the endovascular treatment of carotid artery stenosis. Methods: Electronic bibliographic databases were searched using the words 'micromesh carotid stent'. The review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement standards. Results: The search of the Literature retrieved 84 results. After assessment of full texts, 13 papers were included in the study. The analyzed studies included 797 patients, 32.1% of them were symptomatic. The reported technical success rate was 100% in all cases. During early follow-up, complications occurred overall in 16/797 patients (2%: 12 strokes, 3 deaths, and one transient ischemic attack). The study with the longest follow-up reported a survival rate of 82% at 4 years and a stroke-free survival rate of 84% at 4 years. Conclusion: With the limit of low data quality, the use of dual-layer stents was reported to be as safe and effective at 30 days for the endovascular treatment of extracranial carotid artery stenosis. The reported technical success was 100% in all cases. Further data coming from randomized controlled trials and larger cohort studies with longer follow-up are nevertheless needed for a better evaluation.